The Influence of Work Discipline and Career Development on Employee Performance with Motivation as a Mediating Variable (Case Study at PT. PNM Regional Probolinggo 2) - Arifatur Yuniawati; Siti Safaria (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research determine the role of motivation in influencing work discipline and career development on employee performance of PT PNM Regional Probolinggo 2. The respondents are all account officer employees at PT PNM Regional Probolinggo 2, totalling 371 employees. The technique of sampling using random sampling method which amounted to 100 employees. Method of analysis using SEM and PLS. The results showed that Work Discipline has a positive effect on Work Motivation. Work discipline has no effect on employee performance. Career Development has a positive effect on Work Motivation. Career Development has no effect on Employee Performance. Work Motivation has a positive effect on Employee Performance. Work Discipline affects Work Motivation through Employee Performance. Career Development affects Work Motivation through Employee Performance